The effect of applying picture exchange communication system on autistic bahdini children’s verbal speech - Omer , Yawer; Malo, Sanan (Humanities Journal of University of Zakho, 2022)
The present study aimed to study the effect of the picture exchange communication system on autistic Bahdini children’s verbal speech through a pre-experimental research design. Children with autism spectrum disorder have difficulty in communicating with the people around them. Moreover, autistic children need a special care and attention to be able to communicate and share their feelings and needs with the normal people around them. To conduct the current study, a sample of ten autistic children from Zakho Autism Centre was chosen with the age varying from 3 to 11 years old. Data were collected from the sample adopted via a pre and post-tests. The, data were analyzed in terms of means via the Software SPSS through paired samples-t test. The study also analyzed the verbal speech difficulties encountered by such children. The results arrived at in this study showed that the program had a positive effect on the autistic children’s verbal speech. Based on that, the scores obtained on the post-test showed a statistically significant difference compared to the pre-test scores. In other words, the program helped the children make a progress in their verbal speech. Moreover, this study can help the trainers and teachers at Autism Centers to adopt such a program in their teaching and training with some modifications to fit the context of such centers.